Healthy Living: Checking Blood Glucose - Jennifer Hillan (EDIS)
FCS8811, a 2-page fact sheet by Jennifer Hillan, is for people living with diabetes. It describes who needs to check blood glucose levels, how to do it, and when to do it. A chart is provided for keeping track of readings. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, October 2006.